ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE EOQ: Studi Kasus pada PD Jaya Lestari di Kabupaten Garut - Dwi Yanti Anjani; Barin Barlian; Ari Arisman (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The study aims to see a comparison of raw material inventory at PD Jaya Lestari in Garut Regency before and after using the Economic Order Quantity (EOQ) method. From the results of research that has been carried out on the inventory of materials at PD Jaya Lestari. In determining the inventory of materials, it is carried out conventionally, namely by estimating the amount of raw materials in each acquisition. As a result, the company always experiences an excess in the inventory of its raw materials. The research method used is qualitative using statistical qualit control (SQC) data analysis techniques, the results show that the material inventory control applied by PD Jaya Lestari is not optimal. Where the company can still save inventory costs of Rp.668,097. The number of economical orders (EOQ) for materials is 603,907 kg and the total cost of raw material inventory for production is Rp.48,312,560. The amount of safety reserves for raw materials is 618 kg. Meanwhile, the reordering point for PD Jaya Lestari materials is carried out at the material inventory level at the point of 2064 kg.